Analysis of fatigue levels in semarang state university campus athletes in team sports branch in 2023 - Afthon Nurdin Maulana; Khoiril Anam (Journal Of Sport Education (JOPE), 2023)
(English)This research aims to determine the level of fatigue in Semarang State University campus athletes in futsal and basketball in 2023 using anaerobic test analysis. The research method uses a quantitative research design. The method used in the research is a survey method with test and measurement techniques. The research instrument used RAST (Running-based Anaerobic Sprint Test). The process of methodically collecting and organizing data from field notes, interviews, and documentation is known as data analysis. The results of the research show that the level of fatigue of Semarang State University campus athletes in futsal and basketball in 2023, namely Semarang State University futsal UKM athletes, was obtained by students in the good category with a percentage of 15.2% of the total respondents, students in the fair category with a percentage of 36, 4%, students in the poor category with a percentage of 36.4%, and in the very poor category with a percentage of 12.1%. From the descriptive statistics results, it can be seen that the average fatigue index value for UKM Futsal athletes is 6.46, indicating that the average UKM Futsal athlete is in the low category in measuring the fatigue index. Meanwhile, for Semarang State University basketball UKM athletes, students were found to be in the good category with a percentage of 53.8% of the total respondents, students in the category with a percentage of 38.5%, students in the poor category with a percentage of 7.7%. From the descriptive statistics results, it can be seen that the average fatigue index value for UKM Basketball athletes is 3.77, indicating that the average UKM Basketball athlete is in the adequate category in measuring the fatigue index(Indonesian)Penelitian ini bertujuan untuk mengetahui tingkat kelelahan pada atlet kampus Universitas Negeri Semarang cabang olahraga futsal dan basket tahun 2023 dengan menggunakan analisa tes anaerobik. Metode penelitian menggunakan desain penelitian kuantitatif. Metode yang digunakan dalam penelitian adalah menggunakan metode survei dengan teknik tes dan pengukuran. Instrument penelitian menggunakan RAST (Running-based Anaerobic Sprint Test). Proses pengumpulan dan pengorganisasian data secara metodis dari catatan lapangan, wawancara, dan dokumentasi dikenal sebagai analisis data. Hasil penelitian menunjukkan bahwa tingkat kelelahan atlet kampus Universitas Negeri Semarang cabang olahrag futsal dan bola basket tahun 2023 yaitu atlet UKM futsal Universitas Negeri Semarang, diperoleh mahasiswa dengan kategori baik dengan persentase 15,2 % dari total responden, mahasiswa dalam kategori cukup dengan persentase 36,4%, mahasiswa dalam kategori kurang dengan persentase 36,4%, dan dalam kategori sangat kurang dengan persentase 12,1%. Dari hasil statistik deskriptif dapat dilihat nilai rata-rata indeks kelelahan atlet UKM Futsal sebesar 6,46 menunjukkan dari rata-rata atlet UKM Futsal dalam kategori rendah dalam pengukuran indeks kelelahan. Sedangkan untuk atlet UKM basket Universitas Negeri Semarang, diperoleh mahasiswa yang termasuk dalam kategori baik dengan persentase 53,8 % dari total responden, mahasiswa dalam kategori dengan persentase 38,5%, mahasiswa dalam kategori kurang dengan persentase 7,7%. Dari hasil statistik deskriptif dapat dilihat nilai rata-rata indeks kelelahan atlet UKM Basket sebesar 3,77 menunjukkan dari rata-rata atlet UKM Basket dalam kategori cukup dalam pengukuran indeks kelelahan Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.